Specific and Rapid Detection by Fluorescent In Situ Hybridization of Bacteria in Clinical Samples Obtained from Cystic Fibrosis Patients - Michael Hogardt; Karlheinz Trebesius; Anna Maria Geiger; Mathias W. Hornef; J. Rosenecker; Jürgen Heesemann (2000)
ABSTRACT We report on the rapid and specific detection of bacteria commonly isolated from clinical specimens from cystic fibrosis (CF) patients by fluorescent in situ hybridization (FISH). On the basis of comparative sequence analysis, we designed oligonucleotide probes complementary to species-specific 16S rRNA regions of these microorganisms and demonstrated the specificities of the probes by hybridization of different remotely related as well as closely related reference strains. Furthermore, in a pilot project we investigated 75 sputum samples and 10 throat swab specimens from CF patients by FISH and detected Pseudomonas aeruginosa , Burkholderia cepacia , Stenotrophomonas maltophilia , Haemophilus influenzae , and Staphylococcus aureus within these specimens. The specificity of FISH was 100% in comparison to the results of conventional microbial culture. In contrast, the sensitivity of standard laboratory cultivation was moderately higher, since the limit for microscopic detection of bacteria within sputum samples by FISH was approximately 4 × 10 5 CFU/ml of sputum (resulting in a 90% sensitivity for FISH). Moreover, we demonstrated that FISH will be useful for the rapid detection of bacteria that cause acute pulmonary exacerbations in CF patients, as demonstrated in patients with H. influenzae , S. aureus , and P. aeruginosa exacerbations. Therefore, FISH is a valuable additional method for the rapid and specific detection of bacteria in clinical samples from CF patients, in particular, patients with pulmonary exacerbations.